On the Cell Entropy Inequality for the Fully Discrete Relaxing Schemes (Journal of Computational Mathematics, 2001)
In this paper we study the cell entropy inequality for two classes of the fully discrete relaxing schemes approximating scalar conservation laws presented by Jin and Xin in [7], and Tang in [14], which implies convergence for the one-dimensional scalar case.
Keywords: The relaxing schemes; Entropy inequality; Conservation laws.